Wellness tourism - Buzmakova, Catherine (My University, 2014)
Wellness tourism is travel for the purpose of promoting health and well-being through physical, psychological, spiritual, or emotional activities. Each trend bears relevance to today’s consumer, focusing upon new wellness designs, programs and service levels in air transit, hotel accommodations and destinations.
Keywords: wellness tourism; promoting health; tourism; оздоровчий туризм; зміцнення здоров'я; туризм; оздоровительный туризм; укрепление здоровья